1997
DOI: 10.1093/nar/25.5.1002
|View full text |Cite
|
Sign up to set email alerts
|

The Fission Yeast UVDR DNA Repair Pathway Is Inducible

Abstract: In addition to nucleotide excision repair (NER), the fission yeast Schizosaccharomyces pombe possesses a UV damage endonuclease (UVDE) for the excision of cyclobutane pyrimidine dimers and 6-4 pyrimidine pyrimidones. We have previously described UVDE as part of an alternative excision repair pathway, UVDR, for UV damage repair. The existence of two excision repair processes has long been postulated to exist in S.pombe, as NER-deficient mutants are still proficient in the excision of UV photoproducts. UVDE reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…Also, the extents of induction were comparable; when normalized to control leu1 ϩ mRNA, and compared to uninduced mRNA levels, the maximal observed uve1 ϩ mRNA inductions were 3.4-fold in wild type and 3.7-fold in rad9 mutant cells. This indicates that the elevation of UVDE activity in rad9 mutants is the result of a posttranscriptional regulation which functions in addition to the previously reported transcriptional regulation of uve1 ϩ following UV treatment (7).…”
Section: Rad12supporting
confidence: 59%
See 1 more Smart Citation
“…Also, the extents of induction were comparable; when normalized to control leu1 ϩ mRNA, and compared to uninduced mRNA levels, the maximal observed uve1 ϩ mRNA inductions were 3.4-fold in wild type and 3.7-fold in rad9 mutant cells. This indicates that the elevation of UVDE activity in rad9 mutants is the result of a posttranscriptional regulation which functions in addition to the previously reported transcriptional regulation of uve1 ϩ following UV treatment (7).…”
Section: Rad12supporting
confidence: 59%
“…Whole-cell extracts were prepared from 10 9 S. pombe cells as described previously (7). The protein concentrations of extracts prepared this way were approximately 20 to 30 mg/ml.…”
Section: S Pombe Genetic Manipulations S Pombe Was Cultured By Stamentioning
confidence: 99%
“…studies provide interesting implications for the role of the polyalanine tract in the control of rhp51 ϩ transcription. Several S. pombe genes, including uvi15 ϩ , uvi31 ϩ , UVDE, and rhp16 ϩ , are DNA damage-inducible genes (5,14). Of these, uvi31 ϩ , UVDE, and rhp16 ϩ contain a putative sequence homologous to DRE rhp51 ϩ (5, 14, 37), suggesting the presence of a DDR controlled by DRE rhp51 ϩ.…”
Section: Discussionmentioning
confidence: 99%
“…In lower eukaryotes, studies with the budding yeast Saccharomyces cerevisiae have identified a large number of damageinduced genes, including many involved in DNA metabolism and DNA repair (Aboussekhra et al, 1996;Gasch et al, 2001). In the distantly related fission yeast Schizosaccharomyces pombe, rhp51 ϩ , uvi15 ϩ , uvi31 ϩ , UVDE ϩ , and rhp16 ϩ have been shown to be DNA damage inducible (Bang et al, 1996;Davey et al, 1997;Shim et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In lower eukaryotes, studies with the budding yeast Saccharomyces cerevisiae have identified a large number of damageinduced genes, including many involved in DNA metabolism and DNA repair (Aboussekhra et al, 1996;Gasch et al, 2001). In the distantly related fission yeast Schizosaccharomyces pombe, rhp51 ϩ , uvi15 ϩ , uvi31 ϩ , UVDE ϩ , and rhp16 ϩ have been shown to be DNA damage inducible (Bang et al, 1996;Davey et al, 1997;Shim et al, 2000).DNA damage checkpoint pathways function to delay the eukaryotic cell cycle in response to DNA damage, thus providing an opportunity for DNA repair. Central to the DNA damage checkpoint pathway are two highly conserved phosphoinositol-related kinases, Ataxia telangiectasia mutated (ATM) and ATM and Rad3-related (ATR) and their yeast homologs SpTel1 and SpRad3 in S. pombe, and ScTel1 and ScMec1 in S. cerevisiae.…”
mentioning
confidence: 99%